Antioxidant activity of local Gompang Batu Plants (Lobelia nummularia Lam) in vitro DPPH Method - Ester Basani Panggabean; Murniaty Simorangkir (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
Free radicals are reactive atoms or molecules because they contain unpaired electrons that easily attack body structures, causing various diseases such as cancer, liver, heart and other degenerative diseases. Antioxidants are compounds or molecules that can reduce free radicals. Natural antioxidants are needed to reduce the effects of using synthetic antioxidants. The local plant gompang batu (Lobelia nummularia Lam) is found in Ruhut Bosi Village, Pangaribuan District and has been used by the community as a traditional medicine. This study aims to determine the content of secondary metabolites and antioxidant activity of ethanol extract of gompang batu in vitro using the DPPH (2,2 diphenyl-1-picrylhydrazyl) method. The results of the phytochemical screening test of the gompang batu plant contain secondary metabolites of flavonoids, alkaloids, steroids/terpenoids and saponins. The results of the antioxidant activity test of the ethanol extract of gompang batu obtained an IC50 value of 135,095 ppm (moderate category) and an IC50 value of vitamin C (as a positive control) of 39,390 ppm.